Purchase Interest as a Mediation Variable of Live Streaming And Halal Labeling on Customer Loyalty Towards Emina Products on Tiktokshop (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
The development of social media-based e-commerce, especially TikTok Shop, has created new challenges and opportunities in building customer loyalty, especially in the highly competitive local cosmetics industry. One of the most popular local brands is Emina, which targets young consumers with an affordable price approach and halal label. However, the level of customer loyalty is still a crucial issue that needs to be strengthened so that business sustainability is maintained. The urgency of this research lies in the need to understand how live streaming and halal labeling, as two relevant marketing strategies in the digital era, are able to shape purchasing interest that leads to customer loyalty. This study uses a quantitative approach with the PLS-SEM technique to test the relationship between variables with 115 TikTok Shop user respondents in Semarang City. The results show that live streaming and halal labeling have a significant effect on purchasing interest and customer loyalty, and purchasing interest is proven to mediate the relationship between the two variables and customer loyalty. These findings indicate the importance of integrating interactive visual approaches and religious belief values in digital marketing strategies for cosmetic products.